Postnatal growth in preterm infants: a comparative analysis for gestational age of underweight versus normal weight and small versus normal head size: Postnatal growth in LBW infants - Alyafei, Fawzia; Soliman, Ashraf T; De Sanctis , Vincenzo; Alaaraj, Nada; Ahmed , Shayma; Hamed , Noor; Alkhori , Fatima; Ali , Hamdy; Alyousef, Doaa; Shaat , Mona; Itani , Maya (Acta Biomedica Atenei Parmensis, 2024)
Introduction: Head circumference (HC) is considered a reflection of intracranial volume and brain size, influencing early infant growth. Objectives: We conducted a two-year study on 65 preterm infants (Gestational Age, GA: 33.5 ± 2.2 weeks, birth weight 1.5-2.5 Kg) categorized at birth into underweight z-score (WAZ <-2) and normal weight z-score (WAZ > -2) groups. They were further divided by head circumference for gestational age z-score (HCZ) (<-1 vs. >-1). Results: Preterm infants with birth WAZ <-2 displayed significant improvements in WAZ at 6 and 12 months, transitioning from -2.8 to -1.5 and -1.1, respectively. Although there was an initial decrease in length-for-age z-score (LAZ), during the first 6 months, these infants exhibited catch-up, improving from -1.5 to - 0.2 Z-score. Weight-for-length z-score (WLZ) improved from -5 at birth to -0.6, -0.84, and -0.47 at 6, 12, and 24 months, respectively. Preterm infants with birth WAZ > -2 experienced a decrease in WAZ during the first 6 months but gradually increased afterward. LAZ initially decreased but improved in subsequent months. WLZ exhibited an upward trend. At birth, infants with smaller HCZ were shorter and lighter, and this trend persisted throughout the first and second year of follow-up. Conclusion: Rapid catch-up in WAZ and LAZ was more pronounced during the first year in preterm infants born underweight for their gestational age. However by the end of the second year, those with small HCZ at birth were shorter and lighter at 2 years compared to those with HCZ >-1.